Cognitive pathways to the forms and functions of aggression in adolescence: the role of early maladaptive schemas and social information processing - Vagos, Paula; Fabris, Matteo Angelo; Rijo, Daniel (Frontiers in Psychology, 2025)
IntroductionEarly maladaptive schemas (EMSs) have been found to associate to aggressive behavior, though the cognitive pathways underlying that association remain scarcely investigated, particularly considering the different forms and functions of aggression. The current work explores the sequential mediation pathways linking EMSs and variables related to social information processing (SIP; i.e., hostile attribution of intent and evaluation of overt and relational responses) to aggressive behaviors.MethodsA sample of 516 adolescents (Mage = 16.54, 69.4% female) filled in self-report questionnaires on EMSs, SIP, and the forms and functions of aggression. A model generation approach based on retaining only significant direct pathways was applied to four mediation models that differed in the outcome variable: reactive overt aggression, proactive overt aggression, reactive relational aggression, and proactive relational aggression.ResultsResults showed the salience of EMSs within the disconnection and rejection and the impaired limits domains and of a positive evaluation of aggressive response options. Alternatively, specific results were found for hostile attribution of intent in relation to relational aggression regardless of its function, for reactive overt aggression, and for proactive overt aggression (e.g., hostile attribution of intention impacted indirectly on relational aggression, directly on reactive overt aggression and did not impact on proactive overt aggression).DiscussionOverall and specific findings are discussed based on both developmental (e.g., early neglectful or punitive experiences) and current interaction processes (e.g., social or personal gains associated with the practice of aggressive behavior). Overall, adolescent aggression seems sustained by cognitive pathways that may be more malleable to change based on joint intra and interpersonal intervention efforts.